Tracking Jianghuai Cyclones in China and Their Climate Characteristics - Lan Xia; Yue Zhou (Atmosphere, 2018)
A Jianghuai cyclone is an extratropical cyclone, which influences the middle and lower reaches of the Yangtze River and Huai River basins in China. According to the definition of Jianghuai cyclones, statistics of their climate characteristics from 1979 to 2010 are obtained by an objective detection and tracking algorithm using ERA-Interim reanalysis data. The results show that the frequency of Jianghuai cyclones has a strong year-to-year variability but no obvious trend. Jianghuai cyclones are most frequent in May but fewest in December. As the cold air is active in spring, which interacts with the warm air from the southwest of the subtropical high at the Yangtze-Huai River region, it makes Jianghuai cyclones occur more frequently in this season. The main origins of Jianghuai cyclones are located in the Poyang Lake region, Dongting Lake region, and Dabie Mountain area. The maximum deepening rate of 0–2 hPa/6h is featured in 66.4% of Jianghuai cyclones. Over 40% of Jianghuai cyclones have a mean deepening rate of 0–1 hPa/6h. The lifetime of Jianghuai cyclones is short, mainly lasting for one to two days. In addition, background characteristics are compared between the formation, climax, and decaying periods of Jianghuai cyclones.